Educational attainment and prescription drug misuse: The importance of push and pull factors for dropping out. (January 2020) - Ford, Jason A.; Pomykacz, Corey R.; Ortiz, Kasim; McCabe, Sean Esteban; Schepis, Ty S.
Abstract: Purpose: Young adults who do not complete high school are at increased risk for substance use and offending behavior. A limitation of this research is that dropouts are often treated as a homogeneous group, which ignores the various push (e.g., academic failure or disciplinary problems) and pull (e.g., family responsibility or economic need) factors for leaving school. Methods: The current study relies on multiple years of data from the National Survey on Drug Use and Health (2009–2014) and examines several dependent variables, including prevalence of prescription drug misuse, frequent prescription drug misuse, and prescription drug-related substance use disorder symptoms. We assess the importance of push and pull factors for dropping out, and compare dropouts to respondents who completed school. Results: Multivariable logistic regression analyses produce two important findings. First, push factors increase the risk of various types of prescription drug misuse compared to pull factors. Additionally, respondents who attend college are at a decreased risk for various types of prescription opioid and sedative/tranquilizer misuse and disorder. Discussion: The current research identifies important differences in prescription drug misuse and disorders among dropouts based on the reason they left school. Additionally, college attendance appears to be a strong protective factor. Highlights: Dropping out of school due to push factors increases risk of prescription drug misuse. Dropping out of school due to pull factors decreases risk of prescription drug misuse. A college education is a protective factor for prescription drug misuse.